2008
DOI: 10.1590/s1516-14392008000100010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of grain size and additions of Al and Mn on the magnetic properties of non-oriented electrical steels with 3 wt. (%) Si

Abstract: The influence of hot-band grain size and additions of aluminum and manganese on the magnetic properties of non-oriented grain (NOG) low-carbon electrical steel with about 3 wt. (%) Si were investigated using optical microscopy and X ray diffraction. The addition of manganese resulted in larger grains after final annealing. Coarse grains in the hot-band and addition of Mn led to a Goss orientation component after final annealing, which resulted in an increase in the magnetic permeability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…On the other hand, the initial grain size is another important factor, and it is much easier to form shear bands after deformation in the sheets with initial coarse grains than fine grains [2][3][4][9][10][11][12][13] . So the relatively large initial grain size above 80 µm through the normalized hot band thickness is very favorable for the formation of shear bands.…”
Section: Formation Mechanism Of Dominant Goss Recrystallization Textumentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the initial grain size is another important factor, and it is much easier to form shear bands after deformation in the sheets with initial coarse grains than fine grains [2][3][4][9][10][11][12][13] . So the relatively large initial grain size above 80 µm through the normalized hot band thickness is very favorable for the formation of shear bands.…”
Section: Formation Mechanism Of Dominant Goss Recrystallization Textumentioning
confidence: 99%
“…It is known that γ grains mainly nucleate at the grain boundaries of γ deformed grains [5][6][7][8] , and some investigations [2][3][4][5][9][10][11][12][13][14] have revealed some efficient ways to decrease recrystallization γ fiber. Lee et al [2][3][4] reported that increasing the initial grain size can weaken recrystallization γ fiber by reducing the volume of grain boundaries in Fe-2 wt.% Si alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum has a similar increasing effect on the electrical resistivity but also lowers the permeability of the material. A higher manganese content leads to larger grains and thus a higher permeability, but increases the losses as well [17].…”
Section: Silicon-iron (Sife)mentioning
confidence: 99%
“…Manganese is supposed to retards the development of grains with (111) components and favors the development of grains having (100), (200) and (110) texture components [21,43], leading to an improvement of the magnetic properties of these steels.…”
Section: Effect Of Decarburization Annealing On Crystallographic Texturementioning
confidence: 99%